2-methylindole analogs as cholinesterases and glutathione S-transferase inhibitors: Synthesis, biological evaluation, molecular docking, and pharmacokinetic studies - Cetin, Adnan; Bursal, Ercan; Turkan, Fikret (Elsevier, 2021)
In this study, we aimed to (i) synthesize new 2-methylindole analogs containing various amino structures, pyrrolidine, piperidine, morpholine, and substituted phenyl groups through structural and molecular modifications, (ii) evaluate the pharmaceutical potential of 2-methylindole analogs via assessing enzyme inhibitory activity against glutathione S-transferase (GST), acetylcholinesterase (AChE), and butyrylcholinesterase (BChE), (iii) predict ADMET and pharmacokinetic properties of the synthesized 2-methylindole analogs, (iv) reveal the possible interactions between the synthesized 2-methylindole analogs with GST, AChE, and BChE enzymes using several molecular docking software. In vitro enzyme inhibition assays showed that the synthesized indole analogs exhibited moderate to good inhibitory activities against GST, AChE, and BChE enzymes. Briefly, the inhibitory activities of the analogs 4b and 4i against AChE, 4a and 4b against BChE, and analogs 1 and 4i against GST were detected to be higher or close to the standard inhibitor compounds. The analog 4b was detected to have the best inhibitory activity against both AChE and BChE enzymes with the lowest IC50 values as 0.648 mu M for AChE and 0.745 mu M for BChE. The analyses of enzyme inhibition relationship with the synthesized analogs could help to design new analogs for the inhibitors of cholinergic and glutathione pathways based on the indole derivatives. (C) 2021 Published by Elsevier B.V. on behalf of King Saud University.
Keywords: Acetylcholinesterase; Computational studies; Drug design; Enzyme inhibition; Molecular docking; Therapeutic Efficacy; Indole; Acetylcholinesterase; Antibacterial; Derivatives; Trial; Drug